Assessing Quality Assurance Practices in Institutions of Higher Learnings - Dei, De-Graft Johnson (International Journal of Learning, Teaching and Educational Research, 2019)
In the effort to globalize higher education services and embark on innovative knowledge production and dissemination aimed at fitting into the global scheme, quality assurance becomes the sine qua non. Quality assurance (QA) provides the tools and direction to improve the quality of knowledge created, stored and shared at institutions of higher learning. This study assesses the development and practice of QA in institutions of higher learnings (IHLs) in Ghana. The mixed research method was used to collect data from staff and officers of institutions of higher learning who are directly involved ensuring quality in the institutions. Six (6) IHLs participated in this study. The results indicated a generally higher degree of awareness and understanding of the concept of QA at the institutions as all of them have QA department. The institutions are putting in more effort to ensure quality by carrying out internal assessment as there are available policies and strategies aimed at ensuring quality at the institutions. This led to high service quality at the institutions except for the college of health. Besides, the focused areas quality at the institutions: stated vision, mission; governance structure; statutes and conditions of service; academic and programs; clean and siren environment; staffing; and library, technology and information services. Despite these, the study established that the quality assurance units of the institutions lacked the necessary resources (technology, library, staff, laboratories, etc) for effective quality assurance activities. https://doi.org/10.26803/ijlter.18.12.3